PENINGKATAN BRANDING PRODUK KELOMPOK TANI MUSTIKA MELALUI INOVASI SMART & ANTI-COUNTERFEIT PACKAGING - Nian Gani, Ariel; Nugroho, Randhy; Rofi'i, Muhammad (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This community service program aims to strengthen the market competitiveness of hydroponic products produced by Kelompok Tani Mustika in Kramatjati, East Jakarta, through the implementation of smart and anti-counterfeit packaging innovations. Despite having superior product quality compared to conventional produce, the group struggles to expand its market due to weak branding and the absence of packaging that provides added value and product security. The program was carried out through training, mentoring, and hands-on implementation of branding-oriented packaging design, followed by the development of smart packaging equipped with QR-based product authentication. A web application was also developed to verify product authenticity and integrated with a customer loyalty system that rewards buyers who scan the QR code during purchase validation. The results show a significant improvement in participants’ understanding of branding and packaging, supported by full adoption of smart labels on hydroponic products. This initiative has strengthened consumer confidence, enhanced brand identity, and increased product value to access higher-standard market segments such as restaurants and hotels. Dissemination through mass media and ongoing journal preparation ensures the sustainability and academic contribution of the program. Overall, this initiative successfully strengthens the digital branding capacity, product security, and business sustainability of Kelompok Tani Mustika.